A procedure of school inclusion of a blind child (Práxis Educativa, 2019)
The overall objective of this study was to evaluate the effect of intervention procedures, in the inclusive school environment, on motor development and on the repertory of the social interaction of a blind child with sighted children. A five-year-old male child with developmental delay and his sighted classmates that attended the nursery class of a day care center participated in this study. In order to assess the motor development of the blind child, measurements before and after the intervention, using the Operationalized Portage Inventory and also manual and video recordings were performed. To assess the effects of the intervention on social interaction, contact and exchanges among the child and peers were identified in the filmed sessions. After the intervention, it was found that motor performances and interactive behaviors were included in the blind child’s repertoire, enabling his active participation in the school environment.Keywords: Special Education. School Inclusion. Blind child. Social interaction.